Keterlibatan Sipil (Civic Engagement) Dalam Pelaksanaan Program Bantuan Sosial Rumah Tidak Layak Huni - Sulton Sulton (Universitas Muhammadiyah Ponorogo, 2023)
This research was conducted to get an overview of the forms of civic involvement in the implementation of the Social Assistance for the Rehabilitation of Uninhabitable Houses (BS-RTLH) in the Ponorogo district. The approach used in this research is descriptive qualitative, where data is collected through observation, interviews, and documentation techniques. The results of this study show that, amidst the swift flow of individualistic values and pragmatism, civic involvement in the implementation of community-based programs such as BS-RTLH is still very significant. Civic involvement involves all components of society, starting from individuals, community groups, religious mass organizations, to other social institutions such as universities. Forms of involvement are also widespread, starting from: (1) moral involvement, such as providing moral codes, suggestions, considerations, and moral reasoning, especially at the stage of determining prospective beneficiaries. Even moral activity (moral movement) to mobilize material support for the completion of the program; (2) political involvement such as attendance at meetings, communication, and interaction and lobbying to influence the decision-making for determining the recipients of aid as well as in bolstering aid by the government; (3) social involvement such as involvement in activities (labor) in community service, involvement in the form of material assistance, as well as involvement in the form of skills and expertise for the completion of the BS-RTLH program for the target family. Nonetheless, in practice the three forms of involvement are an integral part of the actualization of civil involvement that cannot be separated.